Identify the Message of Ursula Le Guin’s The Ones Who Walk From Omelas though Its Thematic Structure - Putri Ayu Rezkiyana (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2017)
The Ones Who Walk from Omelas is a science fiction short story written by Ursula Le Guin. The story is about the socio-cultural condition in a city named Omelas. It describes not only the beauty of the city when they are holding a festival, but also the unseen picture that portrays contradiction rather than the festive event people celebrate in. By doing a thematic analysis, the writer in this study is going to convey the message brought by the story writer. This study is under the Halliday’s Systemic Functional Grammar (SFG) focusing on the textual metafunction. There are two research questions suggested in the analysis. The first is what types of theme and mood contained in the story, and the second one is what messages by which the author wants to deliver. The theme, at the very first place, is divided into two categories based on the subject default, which are unmarked and marked theme. Besides, theme is classified into three types of meaning; experiential, textual, and interpersonal theme. For the mood analysis, there are three kinds of mood which are declarative, imperative, and interrogative. In the findings, it is found that the writer ends to use declarative mood in the story to describes the condition, while the imperative mood is used to invite the readers to follow the speaker’s ideas and the interrogative mood is to criticize the society. Besides, the author also tends to apply unmarked theme and preposed theme construction in the story.